A Study of Factors Effecting to Work Efficiency of Employees (Labor Group) in Thai Leather Industry to Success - WorakamolWisetsri, Maaz Ud Din, Dr. Thanyanant Chansongpol, Dr. Keratiwan Kalayanamitra, Dr. Chanyanan Somtawinpongsai (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This research aims to study personal factors including to gender, age, education level, employment conditions, work experience and companies that can effect to work efficiency of workers in the Thai leather industry to success. The aims to study the correlation between motivation factors and work efficiency of the employees in the Thai leather industry to success by using qualitative research methods and using in-depth research based on semi-structured questions. The samples were of executives or entrepreneurs in the Thai leather industry in Bangkok and operate in the leather industry with over 5 years of experience in the leather industry and a total of 10 peoples and using a qualitative data analysis method. The research findings found the factors effect to the performance of employees (labor) in the Thai leather industry to be successful.